A novel Index of Vulnerable Homes: Findings from application in Spain. Issue 3 (March 2020) - Castaño-Rosa, Raúl; Solís-Guzmán, Jaime; Marrero, Madelyn
This paper develops a novel index of vulnerable homes in terms of fuel poverty that is based on the analysis of different existing fuel poverty indicators and their relationship to the residential sector. The new index of vulnerable homes unifies the many indicators hitherto employed, and assesses the home vulnerability situation regardless of whether or not it is in fuel poverty by using three dimensions: monetary cost, energy and thermal comfort. The monetary dimension analyses vulnerability in relation to the available net income to face everyday life. The energy variable assesses the vulnerability related to the constructive characteristics of the dwelling. Finally, the introduction of the thermal-comfort variable enables the evaluation of the vulnerability related to the inner temperature of the dwelling and its perception by occupants. The combination of the different resulting values in each dimension and its relationship to the quality of life of occupants establishes a hierarchy of vulnerable levels. As a result, a multi-dimensional index is defined which relates technical aspects (characteristics of the dwelling) and social aspects (quality of life of households). The index of vulnerable homes provides a more complete assessment of the home situation than the existing fuel poverty indicators by identifying which variables require a greater assistance.